A systems approach for assessing water conservation potential through demand-based water tariffs. (1st April 2017) - Sahin, O.; Bertone, E.; Beal, C.D.
Abstract: Sustainable and responsive water management policies are essential to provide high-quality, reasonably priced drinking water to consumers at any time, while simultaneously ensuring a profit for the water utility. Such goal can be typically achieved through two different types of policy, namely increasing water supply, or managing water demand; the latter can be performed, among others, through water pricing. Pricing, especially when demand-based, can lead to a behavioural change in customer water use, but it is arduous to introduce for a number of political and social reasons; it is essential to engage with relevant stakeholders to clearly recognize pros and cons of implementing a new water tariff. As a consequence, in this paper, economic and social implications of demand-based tariff structures, and their potential for greater water conservation, are assessed through a participatory approach. The variation of residential water demand and revenue outcomes were simulated through an integrated participatory systems approach by assuming that an inclining block tariff was introduced on the Gold Coast region, Australia. Such connection between price, demand, and revenue is highly complex and the choice of System Dynamics for this modelling exercise is considered ideal as it can explicitly handle the non-linearity, feedbacks and interconnections of such system. The simulation model was developed by collaborating with relevant stakeholders, thus ensuring the logical inclusion of all the relevant inputs and connections. Such model integrates three components, namely revenue forecasting; water billing; and demand feedback sub-model. The results show that: a) the inclining block tariff can effectively lead to behavioural change and water consumption reduction, especially within the high water users group, although the predicted water savings would be lower than when adopting water restrictions; b) customers' feedback to an increased cost can be used to achieve revenue neutrality; c) based on customer feedback and modelling simulations, the ideal proportion of customers to be charged with the second block tariff is 20%, however this can be recalculated and varied during wet seasons or dry seasons to optimise water availability. The developed model allows water planners to explore a wide range of policy alternatives (e.g. alternative pricing scenarios to influence demand) over medium to long-term periods and to optimise best-practice decision making for urban water conservation and management. Highlights: Water demand fluctuations and revenue outcomes due to introducing inclining block tariff were assessed. We use an integrated participatory systems approach including stakeholders engagement and system dynamics model development. Simulations show that inclining block tariffs effectively lead to water demand reduction. The tariff structure can be optimised based on season and water availability.